(untitled) (Innovation & Development in Engineering and Applied Science, 2026)
Government information systems are undergoing a progressive transition from monolithic architectures to microservices-based approaches, driven by the need to enhance scalability, resilience, and continuous delivery capabilities. However, in emerging economy contexts such as Ecuador, this transition is constrained by deficiencies in architectural governance, the coexistence of legacy systems, and the lack of institutional standardization. This study proposes a microservices-based reference architecture for Ecuadorian government systems, complemented by a systematic taxonomy of architectural patterns and anti-patterns derived from a systematic literature review, comparative analysis of distributed architectures, and socio-technical modeling. A mixed-method approach is adopted, integrating: (i) systematic literature review (SLR), (ii) architectural decomposition of government domains, (iii) design pattern classification, and (iv) risk assessment of anti-patterns in distributed environments. The results indicate that, while microservices significantly improve scalability and deployment frequency, they also introduce substantial operational complexity in the absence of robust mechanisms for governance, observability, and distributed data management. As a primary contribution, this study identifies architectural governance as the critical factor for the sustainable adoption of microservices in the public sector, and proposes structured guidelines for its implementation in the Ecuadorian context.